Case report: intraprocedural stent thrombosis in percutaneous coronary angioplasty - Oktaviono, Yudi Her (Folia Medica Indonesiana, 2017)
Stent thrombosis is a rare complication of PCI but associated with STEMI and sudden cardiac death. Intra procedural stent thrombosis (IPST) was defined new or increasing (compared with baseline) thrombus within or adjacent to a deployed stent occurring the index PCI procedure whether occlusive or nonocclusive. We describe a case with double vessel disease who has complication cardiac arrest and intra procedural stent thrombosis in LAD and Left Main coronary artery after deployed stent in bifurcation LAD-D1. Thrombectomy and rescucitation were performed, and the patient completed her hospital course without complications.